Preliminary damage severity evaluation of ground vehicles and covered walkways under collision with a small unmanned aerial vehicle (sUAV) - Mohd Hasrizam Che Man (2022)
It is expected that the use of small drones will increase in urban areas in the future for different purposes such as package delivery, industrial inspection, aerial photography, and security surveillance. However, the increase in sUAV traffic may increase the chance of sUAV failure, and debris from air collisions may fall and endanger the safety of vehicles and pedestrians on the ground. The Finite Element Method (FEM) was employed to simulate and evaluate the severity of damage caused by a collision of sUAV (DJI Phantom III and generic multi-rotor UAV weight) to the windshield and roof cover of the car and covered walkway. Moreover, a series of collision simulations were carried out with different parameters such as crash speeds of the sUAV and driving speeds of the car to study the effect of speeds on the severity of damage to the ground vehicles. It was found the damage severity level of car windshield due to drone crash at higher car forward speed cause more severe damage for same weight category. Further analysis of car roof and covered walkway failure due to sUAV operation also be studied, and the simulation shows no damage to the structures was noticed. However, further study with heavier UAVs is recommended to be performed in the future to have a better understanding of this risk. Insights from this study will guide aviation airworthiness authorities to better understand the damage severity level to land vehicles due to sUAV collisions. At the same time, this will facilitate aviation authorities to formulate regulations for safer sUAV operations.